Susceptibility of Rhipicephalus (Boophilus) microplus to fluazuron (2.5 mg/kg) and a combination of novaluron (2.0 mg/kg) + eprinomectin (0.36 mg/kg) in field studies in Brazil - Maciel, Willian Giquelin [UNESP] (2016)
The present study aimed to determine the susceptibility of 32 R. (B.) microplus populations from Southeast, Midwest and South regions of Brazil, to fluazuron (2.5 mg/kg), administered topically (pour-on). Additionally, five populations (Southeast and Midwest regions) of the southern cattle tick were evaluated using in vivo field studies, regarding their susceptibility to a new combination of novaluron (2.0 mg/kg) + eprinomectin (0.36 mg/kg), administered subcutaneously, compared with two positive controls (fluazuron 2.5 mg/kg and eprinomectin 0.5 mg/kg), both administered topically (pour-on). Selected bovines were allocated to treatment groups on day 0, and block formation was based on arithmetic means of female ticks (4.5–8.0 mm long) counted on three consecutive days (−3, −2 and −1). To evaluate therapeutic and residual efficacies of these formulations, tick counts (females ranging from 4.5 to 8.0 mm long) were performed on days 3, 7 and 14 post-treatment, continuing on a weekly basis until the end of each experiment. Results obtained throughout this study, utilizing field efficacy trials, allowed us to conclude that four R. (B.) microplus populations (including two in the Southeast and two in the Midwest regions) could be diagnosed as resistant, or with low susceptibility, to fluazuron (2.5 mg/kg). Such fact was detected in farms where owners applied products containing this active component on cattle for at least five years, with treatment intervals of 30–55 days during the rainy season. Nonetheless, in vitro studies should be performed in order to reinforce in vivo results obtained on the present study. Regarding efficacy indexes obtained by the association of eprinomectin and the novel molecule novaluron against R. (B.) microplus, none of the trials managed to obtain efficacies superior to 48%. Such results, allied to data obtained by different researchers and previously published in literature, reinforce the perception that maybe these formulations containing novaluron, in the administered dosages and treatment routes, may not be effective tools for controlling R. (B.) microplus. However, future studies must be conducted in order to support such hypothesis. Additionally, all five R. (B.) microplus populations were diagnosed as resistant, or with low susceptibility, to eprinomectin (0.5 mg/kg) as well. Even though fluazuron, administered topically (pour on), is still an excellent active principle to be used against R. (B.) microplus, resistance management strategies should be quickly implemented in order to keep selection pressure in Brazil at a minimum level for this compound.